Identifying Students’ Perceptions on YouTube as Online Media in English for MICE - Suharto, Ririn Pratiwi (Saniya Institute, 2023)
Online learning has been one of crucial topic in the Covid-19 pandemic era. This paper aims to describe the student's perception on the use of YouTube application as online learning media. This research used a descriptive qualitative approach by using survey and discussion. The class of this study was twenty-three students. The questionnaire was analyzed by using Likert-Scale and the interview was analyzed qualitatively. The interview script presented to get students statements about their perceptions of English for MICE online learning via YouTube, whether in positive or negative. The result of this research displays that using YouTube as English for MICE’s online learning media gives many positive effects to the student’s English mastery, such as vocabularies, practices and also increased of their English four skills. Though, frequently pupils had anxiety around deficiencies of internet joining, but this problem perceptibly resolved thriving by them.